Indiferencia de padres de familia y su relación en la autoestima de los estudiantes de primaria de la institución educativa N° 6010210 comunidad de Independencia, Río Amazonas 2024 - Mozombite Pariapaza, Karina (2025)
The main objective of this research was to analyze the relationship between parental indifference and self-esteem in elementary school students. This study used a quantitative, non-experimental and cross-sectional approach, with a descriptive correlational design. The study population consisted of 56 elementary school students and their respective parents. Since we worked with the entire population, the sample was a census sample (100%). Data collection was carried out by means of surveys and structured questionnaires. The main findings of this study revealed the following: There is a significant and high negative relationship between parental indifference and students' self-esteem (Spearman's Rho = - 0, 706**, p<0.01). It is interpreted that, as parental indifference increases, students' self-esteem decreases significantly. These results allow us to accept the hypothesis of the study, confirming the relationship between parental indifference and students' self-esteem.